Participación y pasantía en proyectos internacionales con empresa Gestión 360° edificación Málaga, España (2018)
Internationalization is considered the fourth substantive function of higher education, and the University of America Foundation, through its Department of International Relations ORI (International Relations Orientation), strives to integrate the University with the globalized world, through of strategies that bring students, teachers and the administrative body closer to different experiences, becoming global citizens with broader and more tangible perspectives in the economic, social and cultural context. With this the ORI encourages the academic mobility of students, as from the FUA, in order to acquire disciplinary tools from different perspectives, it is also in charge of managing international agreements that allow expanding the knowledge of both research and social projection.